Analisis Efektivitas Pembayaran Pajak Kendaraan bermotor (PKB) Terhadap Penerimaan Pajak Kendaraan Bermotor - Irsan, Muhammad (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine the level of effectiveness of motor vehicle tax payments and to analyze motor vehicle tax receipts at SAMSAR Medan Selatan. Data collection techniques used in this research are documentation and interviews. The analytical technique used in this research is descriptive statistical analysis and description of interview results. The results showed that the realization of motor vehicle tax revenues was above the target set in the budget at the beginning of the year with the realization value reaching the target and above 100%. Obstacles that need to be considered in increasing the realization of motor vehicle tax revenues are by increasing taxpayer awareness to report their motorized vehicle tax objects, by providing payment relief if on time, and the level of effectiveness of motor vehicle tax receipts at the South Medan SAMSAT is in the quite effective category.